HUBUNGAN POLA ASUH ORANG TUA DENGAN KEJADIAN STUNTING PADA BALITA USIA 12–59 BULAN DI WILAYAH KERJA PUSKESMAS INDERAPURA - Ningsih, Desmila Furnia; Putri, Arfianingsih Dwi; Ririn, Ririn (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Stunting remains a major public health issue in Indonesia, including in the working area of the Inderapura Health Center. This condition arises from long-term nutritional deficiencies due to inadequate parenting, poor dietary intake, and low parental awareness of child development. This study aimed to determine the relationship between parenting styles and the incidence of stunting among children aged 12–59 months in the Inderapura Health Center area. This quantitative study employed a correlational analytic design with a cross-sectional approach. The sample consisted of 54 mothers selected through purposive sampling. Data were collected using a parenting style questionnaire and anthropometric measurements based on WHO standards. Chi-Square tests were conducted to determine the association between variables. The results showed that 44.4% of respondents practiced a permissive parenting style, and 33.3% of these had stunted children. Statistical testing indicated a significant relationship between parenting style and stunting incidence (p = 0.013). In conclusion, parenting style is significantly associated with stunting incidence. Health workers are encouraged to enhance parental education and strengthen the First 1000 Days of Life program to prevent stunting.